PENGETAHUAN DAN SIKAP IBU POST PARTUM NORMAL TENTANG TEHNIK MENYUSUI YANG BENAR DI KLINIK SUNGGAL - Namira Yusuf (Universitas Prima Indonesia, 2019)
The correct breastfeeding technique is how to give milk to the baby by attaching and positioning the mother and baby properly. How to breastfeed greatly affect the comfort of a baby sucking milk. Midwives or nurses need to provide guidance to the mother in the first week after delivery (post partum), about the actual ways of breastfeeding so as not to cause problems. The objective of the research was know the knowledge and attitudes of normal post partum mothers about breastfeeding techniques that are correct at Klinik Sunggal Medan. The research is done by using descriptive approach of 16 samples and use primary and secondary data by distributing questionnaires. The result of the research showed that the majority of respondents have good knowledge as many as 8 people (50%), and lack of knowledge are 2 people (12.5%) and data has been obtained that the majority of positive mother attitudes are 10 people (62.5%) and the minority of respondents have negative knowledge namely 6 people (37.5%). Based on this study it was concluded that the majority of post partum mothers' knowledge of breastfeeding techniques is well-informed, and the majority of mothers have positive attitudes. Respondents are expected to seek information and ask lots of people who have done breastfeeding techniques correctly in adapting during the post partum period